Representation of Islamic values in Asma’ Artho at Fathul Ulum Islamic Boarding School Kwagean Kediri - Diana Mayasari; Rahmat Hidayat (Bahastra)
Islamic boarding schools are renowned for their robust religious culture. Fathul Ulum, a notable Islamic boarding school, conducts an activity known as Asma' Artho (AA) in conjunction with commemorating the Prophet's birthday. This activity is characterized by the integration of monetary benefits and wirid, which has led some to perceive it as contrary to Islamic values. This research aims to elucidate, through an anthropolinguistic lens, that AA embodies Islamic cultural values. By examining the structural patterns of Asma' Artho and its connections to the Al-Quran and Hadith, this study employs a descriptive qualitative method grounded in critical discourse analysis. The findings reveal a macro text structure centered on belief in God and the veneration of the Prophet Muhammad SAW. The text's superstructure includes an introductory tawassul, a core focused on the benefits of wirid, prayer, and sholawat related to wealth, concluding with Al Fatihah. The microstructure highlights semantic elements that request sustenance, wealth, authority, and intercession from the Prophet Muhammad. Co-textual elements reinforce the text's prayer function, supported by both material and non-material aspects, while the context encompasses the prayer leader, recitation, and etiquette. Consequently, AA reflects two cultural values: the practice of selected wirid for financial prosperity and the recitation of Diba’s and Barzanji prayers by the Al-Quran, Hadith, and authentic texts. The study's implications suggest that the wirid series in AA can serve as a prayer procedure for the broader community.